2019
DOI: 10.3389/fpsyg.2019.01465
|View full text |Cite
|
Sign up to set email alerts
|

The Beginning of Senior Career in Team Sport Is Affected by Relative Age Effect

Abstract: Many previous studies in national team sports did not report evidence about relative age effect (RAE) in senior categories. This study aimed for the first time to determine if the RAE may specifically affect the early, but not the late, phase of senior career in elite team sports. A total of 3,319 birthdates (basketball: n = 642; rugby: n = 572; soccer: n = 1318; volleyball: n = 337; water polo: n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
66
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 37 publications
10
66
2
1
Order By: Relevance
“…Because athlete development is a complex and multidimensional process (e.g., Kelly and Williams, 2020 ), it is important to appreciate that there may be other contributing factors that have influenced the balanced BQ distributions throughout the selection levels (e.g., social context, competition level, and the number of active participants; Musch and Grondin, 2001 ). As an example, it has been previously documented that, during a comparison of different youth sports, those with greater popularity often comprise a stronger RAE (Lupo et al, 2019 ). As such, it may be argued that the lower participation levels of squash compared to other sports in England (e.g., soccer) may result in less difficulty during the selection process, and thus, a weaker RAE occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Because athlete development is a complex and multidimensional process (e.g., Kelly and Williams, 2020 ), it is important to appreciate that there may be other contributing factors that have influenced the balanced BQ distributions throughout the selection levels (e.g., social context, competition level, and the number of active participants; Musch and Grondin, 2001 ). As an example, it has been previously documented that, during a comparison of different youth sports, those with greater popularity often comprise a stronger RAE (Lupo et al, 2019 ). As such, it may be argued that the lower participation levels of squash compared to other sports in England (e.g., soccer) may result in less difficulty during the selection process, and thus, a weaker RAE occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Other explanations were as follows: lower dropout rate by relatively young players due to a lower number of injuries than relatively older players (Bjørndal et al, 2018a ), self-improvement experiences associated with adversity in selection processes (Collins and MacNamara, 2017 ), high levels of challenge in competition (McCarthy et al, 2016 ), or player recruitment systems (Sims and Addona, 2016 ). However, it should be clarified that the influence of the birthdate in professional sports (RAE vs. RAE reversal) does not yield results in the same direction, depending on factors connected to the sport context (Delorme et al, 2009 ; Lupo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis confirmed that the RAE had an impact in most sports, both on an individual level and on a team level: for every two subjects born in the last quartile of an age group, more than three of the first quartile of the same age group participated in the same sporting context. The RAE appears to have a large impact on the selection processes associated with TID systems in team sports such as ice hockey [10], basketball [11,12], football [13][14][15], rugby [16], Australian football [17], and handball [18,19]. However, recent research in women´s sports has reported more diverse findings, and the impact of the RAE in these seems to be less extensive [20].…”
Section: Introductionmentioning
confidence: 99%